SOCIAL MEDIA UTILIZATION IN B2B MARKETING COMMUNICATIONS IN PALM OIL PLANTATION RESEARCH SERVICES - Ismy Agustin; Margaretha Mayang Tri Astari; Ema Rosmawati (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The power of social media is utilized by salespeople in shaping an organization's brand image and marketing communications, including B2B organizations. As a commercial Research Institute, SRS utilizes social media like Facebook, Instagram, and LinkedIn in conducting marketing communications and also expanding their market reach. This study is conducted in order to know the influence of social media engagement, especially Facebook, LinkedIn and Instagram, on sales in B2B companies. The data that is used for this study is data for two years which is data from January 2019 - December 2020. The results show that social media engagement (Facebook, Instagram and LinkedIn) jointly affects sales at SRS. Meanwhile, the result of a partial analysis of each SRS social media online engagement (Facebook, Instagram and LinkedIn) show that social media like Facebook does not affect SRS sales, while other social media like Instagram and LinkedIn significantly affect SRS sales.